A virtual reality program to assess cognitive function in multiple sclerosis: A pilot study - Hsu, Wan-Yu; Anguera, Joaquin A.; Rizzo, Albert; Campusano, Richard; Chiaravalloti, Nancy D.; DeLuca, John; Gazzaley, Adam; Bove, Riley M. (Frontiers in Human Neuroscience, 2023)
Introduction: Cognitive impairment is a debilitating symptom in people with multiple sclerosis (MS). Most of the neuropsychological tasks have little resemblance to everyday life. There is a need for ecologically valid tools for assessing cognition in real-life functional contexts in MS. One potential solution would involve the use of virtual reality (VR) to exert finer control over the task presentation environment; however, VR studies in the MS population are scarce. Objectives: To explore the utility and feasibility of a VR program for cognitive assessment in MS. Methods: A VR classroom embedded with a continuous performance task (CPT) was assessed in 10 non-MS adults and 10 people with MS with low cognitive functioning. Participants performed the CPT with distractors (ie. WD) and without distractors (ie. ND). The Symbol Digit Modalities Test (SDMT), California Verbal Learning Test – II (CVLT-II), and a feedback survey on the VR program were administered. Results: People with MS exhibited greater reaction time variability (RTV) compared to non-MS participants, and greater RTV in both WD and ND conditions was associated with lower SDMT. Conclusions: VR tools warrant further research to determine their value as an ecologically valid platform for assessing cognition and everyday functioning in people with MS.